Perbandingan Persepsi dan Praktik Terhadap Aurat di Berbagai Konteks Budaya - Hafilia Muzniyyah; Giani Regina (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Aurat, a concept related to modesty in dress, has a diverse interpretations and practices across the world. This study aims to compare how aurat is perceived and practiced in different cultural contexts. Scholars from various disciplines, such a anthropology, religion and sociology, have long researched the concept of aurat. Previous studies have shown that the definition of aurat, dress practices and perceptions of aurat can very significantly between different cultures. Individual perceptions of aurat, which are influenced by factors such as religiom, tradition, and social norms, can have various consequences, including misscommunication, conflict and cultural change. This researched uses a qualitative methodology with a literature, such a as unity, balace, reedom of choice and responsibility are realized in real life through positive actions. The Qur’an, as the holy book of Muslim, contains guidelines on various aspects of life, including covering the aurat. The perceptions of aurat in the Qur’an has a broader meang than simply covering certain body parts.